The arts, audio visual technology & communications - safran, Pete; Glossbrenner, Alfred; Cambridge Educational (New Jersey : Cambridge Educational, 2004)
This program looks at opportunities to design, produce, exhibit, perform, write or publish in a variety of media and it provides interviews with a cable TV broadcast engineer, newspaper reporter, professional actor, commercial artist, and a TV director/producer.
Camera, Bob Sullivan ; editor, Bob Suravage.
Narrator, Jeannie Stith.
DVD format.
Keywords: Art -- Vocational guidance; Communication -- Vocational guidance; Reporters and reporting -- Vocational guidance; Commercial art -- Vocational guidance